Implementasi Program Character Building Training ( Studi Kasus Mahasiswa Pendidikan Agama Islam Angkatan 2013) - Amri, Muhammad (Inspiratif Pendidikan, 2016)
Character Building Program (CBP) as an institution that can provide guidance and capacity building of students both in the field of intellectual, skills and attitudes. Bids institutional program refers to three things: the resolution of the human relationship with God, the resolution of the human relationship with itself and the resolution of the human relationship with the environment. Directions guidance mentioned above, with the emphasis on resolution improvement of man’s relationship with God will bring the space to give birth attitude obedience and submission to God and the implications for compliance and obedience to others. Resolution on yourself to bring students to identify, develop their potential so that students can be more advanced and competitive. And the resolution of the human relationship with the environment to bring students to recognize and appreciate all the circumstances around it.